Impact of growth trajectory on sexual maturation in layer chickens - Bahry, Mohammad A.; Hanlon, Charlene; Ziezold, Clara J.; Schaus, Sierra; Bédécarrats, Grégoy Y. (Frontiers in Physiology, 2023)
Recent studies showed that apart from photostimulation, metabolic triggers may independently activate sexual maturation and egg production in chickens. However, the origin, mode of action, and specific target(s) of this metabolic control remain unknown. Beyond body weight (BW), we hypothesize that body composition (BC) and associated specific metabolic signals are involved. Thus, this study was conducted to determine the BW and BC thresholds triggering spontaneous sexual maturation in layer pullets under different growth trajectories. Day-old Lohman LSL lite and Lohman brown lite chicks (n=210 each) raised in brooding cages under ad libitum (AL) feeding until 8 weeks of age were randomly allocated into individual cages and assigned to one of 3 experimental growth profiles; AL, breeder’s target (T), restricted 20% below target (R), (n=70 birds/profile/strain). Birds had free access to water throughout the trial. All hens were maintained on 10 h of light (10 lux) throughout the rest of the study. Blood and tissue samples were collected throughout the study to measure plasma estradiol (E2) concentrations and organ weights, respectively. Furthermore, carcasses were subjected to Dual-energy X-ray absorptiometry (DEXA) analyses. All analyses were completed with SAS using the MIXED procedure. Results show that R treatment slowed (P < 0.001) growth, delayed age at first egg (FE) and egg production (P<0.001) and resulted in lower BW at FE (P < 0.001), lower ovary weight and number of follicles (P<0.001) compared to AL in both strains, whereas, the strain significantly impacted body weight (P<0.0001), ovary weight (P< 0.001), BW at FE (P<0.001), age at FE (P<0.001), egg production (P<0.0001), E2 (P<0.0001) and body composition (P<0.05). For DEXA, AL feeding (P<0.001) increased fat deposition compared to R. Furthermore, there was a positive correlation between plasma E2 and bone mineral content (P<0.01) and bone mineral density (P<0.01). In conclusion, feed allocation impacted growth and BC in a strain dependent manner which resulted in differing age at sexual maturation and egg production. Furthermore, a body fat threshold between 10 to 15% appears to be required for the occurrence of spontaneously sexual maturation in laying hens.